The potential protective effects of malacca (Phyllanthus emblica L.) extract against doxorubicin-induced cardiotoxicity in male Wistar rats - ETRINA MELINDA; ERMI GIRSANG; ALI NAPIAH NASUTION (Jurnal Natural, 2021)
Doxorubicin as a chemotherapy agent is most widely used in cancer treatment. Long-term use at a predetermined dose has a side effect, namely cardiotoxicity. Doxorubicin-induced cardiotoxicity is considered to be caused by reactive oxygen species (ROS), which is also characterized by increasing CK-MB enzyme levels in the blood. To reduce the impact of doxorubin-induced toxicity, a study was conducted on natural antioxidant sources with cardioprotective capabilities in vivo. Phyllanthus emblica L. fruit was used as a sample for a natural source of antioxidants extracted using ethanol. Then performed a phytochemical screening of secondary metabolites contained in it. This extract was administered orally in various doses to the experimental animal Wistar rats and the induced doxorubicin to these animals. The CK-MB enzyme levels were measured, and the heart organ histopathology test was performed. The results of this study indicate that P. emblica L. fruit extract contains alkaloids, tannins, flavonoids, terpenoids, phenolics, and triterpenoids compounds. Extract treatment at a 400 mg/kg BW dose showed the best reduction in CK-MB levels with great improvements in regular arrangement and shape of myocardial muscle cells of cardiac tissue. The sample extract at a 400 mg/kg BW dose showed remarkably decreasing of CK-MB great improvements of heart tissue on doxorubicin-induced cardiotoxicity. This study showed the potential protective effect of P. emblica L. against doxorubicin-induced cardiotoxicity.